2013
DOI: 10.1016/j.lungcan.2013.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Development of ferret as a human lung cancer model by injecting 4-(N-methyl-N-nitrosamino)-1-(3-pyridyl)-1-butanone (NNK)

Abstract: Objective Development of new animal lung cancer models that are relevant to human lung carcinogenesis is important for lung cancer research. Previously we have shown the induction of lung tumor in ferrets (Mustela putorius furo) exposed to both tobacco smoke and a tobacco carcinogen (4-(N-Methyl-N-nitrosamino)-1-(3-pyridyl)-1-butanone, NNK). In the present study, we investigated whether NNK treatment alone induces both preneoplastic and neoplastic lesions in the lungs of ferrets. Methods We exposed ferrets t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 39 publications
2
28
0
Order By: Relevance
“…They found that 16.7% of ferrets developed tumors 24 weeks after NNK injection (50 mg/kg), and after 26 and 32 weeks, the proportion increased to 40% and 66.7%, respectively. These results indicated that the injection of NNK alone could induce both preneoplastic lesions (squamous metaplasia, dysplasia, and atypical adenomatous hyperplasia) and tumors (squamous cell carcinoma, adenocarcinoma, and adenosquamous carcinoma) in lung, which were commonly seen in humans [24].…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…They found that 16.7% of ferrets developed tumors 24 weeks after NNK injection (50 mg/kg), and after 26 and 32 weeks, the proportion increased to 40% and 66.7%, respectively. These results indicated that the injection of NNK alone could induce both preneoplastic lesions (squamous metaplasia, dysplasia, and atypical adenomatous hyperplasia) and tumors (squamous cell carcinoma, adenocarcinoma, and adenosquamous carcinoma) in lung, which were commonly seen in humans [24].…”
Section: Introductionmentioning
confidence: 87%
“…Aizawa et al [24] also used this scheme in male ferrets (3-5-month old) without smoke exposure. They found that 16.7% of ferrets developed tumors 24 weeks after NNK injection (50 mg/kg), and after 26 and 32 weeks, the proportion increased to 40% and 66.7%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Given the higher range of NNK contained in some tobacco products as well as the concentration used to provoke neoplastic change in experimental animals studies [18], the concentration used in the current in vitro study (100 mg/ml) was appropriate inasmuch as it provoked phenotypic transitions documented in other studies while retaining cell viability. In vitro cell culture models have been widely appropriated for mechanistic studies of a variety of infectious agents on differing epithelia of humans and experimental animals [19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…The fixed tumor tissues were embedded in paraffin and cut into 3–5 µm sections (20). The experiment was performed on with a streptavidin-peroxidase system (OriGene Technologies, Inc., Beijing, China).…”
Section: Methodsmentioning
confidence: 99%